Lathosterol and Noncholesterol Sterols in Routine Use for the Differentiation and Monitoring of Dietary and Drug Induced Treatment of Hypercholesterolemias in Children and Adolescents - Hyanek, Josef; Pehal, Frantisek; Dubska, Ladislava; Martinikova, Vera; Privarova, Jana; Taborsky, Ludek (Journal of Nutritional Therapeutics, 2014)
Aims: The authors discuss their 15 years of experience with use of noncholesterol sterols (NCS) when diagnosing heterozygous familial hypercholesterolemia (HFH) and the dietary and drug treatment of children and adolescents when lathosterol (Lat) and desmosterol (Des) as cholesterol synthesis precursors, and campesterol (Cam) and sitosterol (Sit) as cholesterol absorption precursors are included. Patients and Methods: 38 children and adolescents (6-18 yrs) with HFH proven by molecular genetic testing of LDL-cholesterol receptor deficit; 107 children patients with clinical and laboratory symptoms of other hypercholesterolemias; 84 healthy school-age children as a control group. Routine lipid spectrum scan—total cholesterol (TCh), LDL-Ch, HDL-Ch, TAG, with additional apo A1, apo B, Lp (a), LDL-receptors, apo E polymorphism; Lat, Des, Cam and Sit in the plasma—was established by means of GC/MS. Results: The HFH patients on a low cholesterol diet (LCHD) who come to our lipid outpatient clinic have elevated levels of Lat and Des, unlike patients with alimentary hypercholesterolemia (p<0, 001). Lat and Des levels are high following interruption of medical treatment during long vacations or when drug treatment is neglected. Administration of statins only in sufficiently high therapeutic doses reduces Lat and Des (p<0, 001). Compensatory elevation of Cam and Sit occurs only in few pediatric patients. Ezetimibe decreases Cam and Sit more efficiently than Lat or Des. Combination of statin with ezetimibe is most efficient in decrease of not only TCh but also Lat and Des, as well as Cam and Sit. Conclusions: Extending the laboratory spectrum by precursors of cholesterol synthesis and absorption improves the differential diagnosis of HFH and makes monitoring and/or treatment of children and adolescents more precise.